Screening of the Argentinean INTA peanut core collection with a molecular marker associated with resistance to Sclerotinia minor Jaggar - Chamberlin, K.D.; Baldessari, Jorge Javier; Mamani, Eva Maria Celia; Moreno, Maria Valeria (2020)
Cultivated peanut, the third most important oilseed in the world, is consistently threatened by various diseases and pests. Sclerotinia minor Jagger (S. minor), the causal agent of Sclerotinia blight, is a major threat to peanut production in many countries and can reduce yield by up to 50% in severely infested fields. Host plant resistance will provide the most effective solution to managing Sclerotinia blight, but limited sources of resistance to the disease are available for use in breeding programs. Peanut germplasm collections are available for exploration and identification of new sources of resistance, but traditionally the process is lengthy, requiring years of field testing before those potential sources can be identified. Molecular markers associated with phenotypic traits can speed up the screening of germplasm accessions. The objective of this study was to genotype the peanut core collection of the Instituto Nacional de Tecnología Agropecuaria (INTA) Manfredi, Argentina, with a molecular marker associated with Sclerotinia blight resistance. One hundred and fifty-four (154) accessions from the collection were available and genotyped using the Simple Sequence Repeat (SSR) marker. Accessions from each botanical variety type represented in the core collection were identified as new potential sources of resistance and targeted for further evaluation in field tests for Sclerotinia blight resistance.